Nexus between Energy Intensity, CO2 Emissions and Food Security: Asymmetric and Symmetric View from Kazakhstan - Syrbek, Perizat; Bimendiyeva, Laila; Kondybayeva, Saltanat; Tlesova, Aigul; Tolepov, Adil (International Journal of Energy Economics and Policy, 2025)
The aim of this study is analyzed nexus between energy intensity, CO2 emissions with food security in Kazakhstan. As dependent Food security indicator food production index and for energy intensity indicator Energy intensity level of primary energy were taken. As socio-economic indicators GDP per capita and population growth are taken. Data cover 2000-2021 years and extracted from World Bank Data and Worldometers. As research methods Nonlinear Autoregressive Distributed Lag (NARDL) Analysis and Linear Autoregressive Distributed Lag (ARDL) were applied. According to NARDL method, Fossil CO2 emissions and GDP per capita found to be main factors from selected ones to affect food production index positively. CO2 emissions (total) have positive effect on Food production index too. According to ARDL method, change in population correlated positively with Food Production index in long term. Energy intensity impacts negatively in short term and positively in long term on Food Production Index. Results imply that in Food production ecofriendly methods and new technology should be prioritized.